2015
DOI: 10.1111/vde.12224
|View full text |Cite
|
Sign up to set email alerts
|

Complementary effect of oral administration of Lactobacillus paracasei K71 on canine atopic dermatitis

Abstract: Oral administration of K71 can be useful in dogs with cAD as a complementary therapy, by providing a steroid-sparing effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…The effect of age when starting probiotic supplementation has not been studied. Previous canine studies initiated supplementation with Lactobacillus at perinatal, juvenile stages, and adulthood and all suggest preventive and drug-sparing effects (Marsella et al 2012, Ohshima-Terada et al 2015. It has yet to be elucidated if and how best to use probiotics in the management of AD in adult dogs, given the paucity of prospective blinded studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of age when starting probiotic supplementation has not been studied. Previous canine studies initiated supplementation with Lactobacillus at perinatal, juvenile stages, and adulthood and all suggest preventive and drug-sparing effects (Marsella et al 2012, Ohshima-Terada et al 2015. It has yet to be elucidated if and how best to use probiotics in the management of AD in adult dogs, given the paucity of prospective blinded studies.…”
Section: Discussionmentioning
confidence: 99%
“…Privately owned dogs previously diagnosed, by a veterinary dermatology specialist or resident, with non-food-induced AD according to accepted exclusion criteria (Deboer & Hillier 2001) and responsive to oclacitinib, were screened for enrolment. Since this was a pilot study, a sample size calculation was not performed, but we sought to enroll 40 patients to align with previously published veterinary studies (Marsella 2009, Ohshima-Terada et al 2015. Before screening, all patients had normal routine biochemistry and haematology profiles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This multicentre, double‐blinded, placebo‐controlled study was performed at 15 hospitals in Japan by 10 veterinarians. Based on a previous report, the size of this study was set at 40 dogs …”
Section: Methodsmentioning
confidence: 99%
“…Gastrointestinal microbiome dysbiosis and the role of microbial modulation in AD development have been of interest . Although the effects of probiotics in the prevention and treatment of AD remain obscure, some reports have shown that oral administration of probiotics, prebiotics or synbiotics can reduce the clinical symptoms or the dosage of medications in human AD, as well as the signs in canine AD (cAD) . Oral administration of lysed Enterococcus faecalis FK‐23 has been mentioned as a potential intervention to reduce allergic responses in mice and humans .…”
Section: Introductionmentioning
confidence: 99%